Clima organizacional y desempeño laboral de los trabajadores de la Municipalidad Provincial de Maynas, año 2021 - Fernandez Mendez, Karen de Isabel (2022)
This thesis shows the relationship between the organizational climate and work performance in the workers of the Provincial Municipality of Maynas, concerning the period of 2021. To carry out the research, the "Organizational Climate" questionnaires of Sonia Palma (1999) and Price's Job Satisfaction, conditioned by Alarco (2010) in the Peruvian context. The survey was carried out on 285 workers of the Provincial Municipality of Maynas, concerning the period of 2021, answered in a single moment individually and privately. The results obtained show that the value of Spearman's Rho is 0.418?? presenting a significant correlation, the value of sigma (bilateral) is 0.00 the same as being less than 0.05 it is interpreted that the alternate hypothesis (????) and the null hypothesis (??0) is rejected, 285 records processed are presented. This allows us to affirm that the general hypothesis is approved because there is a relationship between the organizational climate and job performance in the workers of the Provincial Municipality of Maynas, year 2021, is approved. It´s expected that the thesis will serve as a reference tool for policies of management and leadership in this important unit, thus they will be able to improve the interns for the annual evaluation of the general performance of the organization, leading to an improvement in production., towards society, of the Provincial Municipality of Maynas.